Everything is predictable : how Bayesian statistics explain our world - Chivers, Tom (Science writer) (One Signal Publishers/Atria, 2024)
"At its simplest, Bayes's theorem describes the probability of an event, based on prior knowledge of conditions that might be related to the event. But Tom Chivers lays out how it affects every aspect of our lives. He explains why highly accurate screening tests can lead to false positives and how a failure to account for it in court has put innocent people in jail. But its influence goes far beyond practical applications. A cornerstone in rational thought, Bayesian principles are used in modeling and forecasting....And many argue that Bayes' theorem is not just a useful tool, but a description of almost anything -- that it is the underlying architecture of rationality...Fusing biography, razor-sharp science writing, and intellectual history, Everything is Predictable is an entertaining tour of Bayes' theorem and its impact on modern life, showing how a single compelling idea can have far-reaching consequences" -- Book jacket.